Sinh địa tầng Nanoplankton Cácbônát (Nannofossils) trầm tích đáy bồn trũng Nam Côn Sơn - Nga, Đặng Đức; Vinh, Nguyễn Văn (VNU Journal of Science: Natural Sciences and Technology, 2004)
More than 100 species of more 20 genus Calcareous nannoplankton fossils in sediments of the Nam Con Son basin are founded at the first time. They are categoried as follows: Cyclicargolithus abisectus -Discoaster deflandrei assemblage (superbiozone) of over part of the formation Cau - under part of the formation Dua; equivalent zones from NP24 to NN! (Martini,1971), from CP19 to CNla-b (Bukry,1981), most of the stages Chati and Aquitan; has age late Oligoxen - early part of early Mioxen; - Biozones: Discoaster druggii, Sphenolithus belemnos, Helicosphaera ampliaperta, Sphenolithus heteromorphus, Helicosphaera philippinensis, Discoaster kugleri, Catinaster coalitus, Discoaster hamatus, Discoaster bellus, Discoaster quinqueramus of over - middle part of the formation Dua, the formation Thong - Mang cau, the formation Nam Con Son, equivalent zones fromNN2 to NNll (Martini,1971),from CNlc to CN9 (Bukry,1981), stages Burdigal, Langhi, Seraval, Torton and Messin; has age Mioxen; - Biozones: Discoaster mendomobensis, Ceratolithus rugosus, Reticulofenestra psudoumbilica, Discoaster brouweri most of the formationBien Dong, equivalent zones from NN12 to NN18 (Martini, 1971), from CN10 to CN12 (Bukry), stages 7 Zancli, Piaxen; has age Plioxen; - Biozones: Crenalithus doronicoides, Gephirocapsa oceanica, of over part of the formation Bien Dong, equivalent zones from NN19 to NN20 (Martini,1971), from CN13 to CN 14 (Bukry,1981), stage Calabria; has age Pleistoxen.